Real-World Assessment of Weight Change in African American Females and Hispanics with HIV-1 After Initiating Integrase Strand-Transfer Inhibitors or Protease Inhibitors - Yen-Wen Chen; David Anderson; Christopher D. Pericone; Prina Donga (Journal of Health Economics and Outcomes Research)
**Background:** Studies have shown an increase in weight among people living with HIV (PLWH) who initiated integrase strand transfer inhibitors (INSTI). However, weight gain with INSTI-based regimens vs other regimens in females or racial/ethnic minorities is poorly understood.